Mereview Arah Undang-Undang Perbankan Syariah di Indonesia - A. Zuliansyah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2011)
The application of Islamic law in the activities of banking/finance  or  other modern economic activities is not a simple job. The study of the banking law, or sharia  finance law to be an interesting study and challenging for the world of law in Indonesia, where the positive law (law) in the country of Indonesia is different from  that applicable to the religious law  (Islam). Enforcement of religious law (Islam)  must go through a process referred to as  the ”positivisasi” Islamic law. In this case, Islamic law accepted by the state  in  positive laws and regulations that apply  nationally. This paper will examine  the law of Law no. 10 of 1998 concerning Amendment to law number 7 of 1992. Likewise, Law number 21 of 2008 has some interesting general provisions to be observed. General provisions referred to (Article 1) is a novelty and will  provide certain implications